2021
DOI: 10.3390/antiox10071094
|View full text |Cite
|
Sign up to set email alerts
|

A Novel mRNA-Mediated and MicroRNA-Guided Approach to Specifically Eradicate Drug-Resistant Hepatocellular Carcinoma Cell Lines by Se-Methylselenocysteine

Abstract: Despite progress in the treatment of non-visceral malignancies, the prognosis remains poor for malignancies of visceral organs and novel therapeutic approaches are urgently required. We evaluated a novel therapeutic regimen based on treatment with Se-methylselenocysteine (MSC) and concomitant tumor-specific induction of Kynurenine aminotransferase 1 (KYAT1) in hepatocellular carcinoma (HCC) cell lines, using either vector-based and/or lipid nanoparticle-mediated delivery of mRNA. Supplementation of MSC in KYAT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 50 publications
0
11
0
Order By: Relevance
“…KYAT1 uses MSCs as substrates to generate two metabolites, MS and MSP, both of which have antitumor and antiproliferative properties ( Rooseboom et al, 2001 ; Lee et al, 2009 ; Zeng, 2009 ). MicroRNA-guided tumor-specific induction of KYAT1 combined with the MSC has great potential in treating cancers beyond cure ( Selvam et al, 2021 ). As part of the complement system, CR1 was a master regulator of complement activation, chronic inflammation, and innate immune responses ( Jurianz et al, 1999 ).…”
Section: Discussionmentioning
confidence: 99%
“…KYAT1 uses MSCs as substrates to generate two metabolites, MS and MSP, both of which have antitumor and antiproliferative properties ( Rooseboom et al, 2001 ; Lee et al, 2009 ; Zeng, 2009 ). MicroRNA-guided tumor-specific induction of KYAT1 combined with the MSC has great potential in treating cancers beyond cure ( Selvam et al, 2021 ). As part of the complement system, CR1 was a master regulator of complement activation, chronic inflammation, and innate immune responses ( Jurianz et al, 1999 ).…”
Section: Discussionmentioning
confidence: 99%
“…Notably, TEER values in media culture without Caco-2 cells were used as a blank and were subtracted from the values for the measurements. For measurement of malondialdehyde (MDA; an indicator of reactive oxygen species of lipid peroxidation) [ 105 ], the activated Caco-2 cells were homogenized by the Ultra-Turrax homogenizer (IKA, Staufen, Germany) and centrifuged at 12,000× g for 15 min at 4 °C to separate the supernatant. Then, malondialdehyde (MDA) in the supernatant was measured by an MDA assay kit (colorimetric) (Abcam, Cambridge, UK) according to the manufacturer’s protocol and representing the intracellular reactive oxygen species (ROS).…”
Section: Methodsmentioning
confidence: 99%
“…MSC is both a transaminase and β-lyase substrate of GTK, although transamination is somewhat more favored over the β-lyase reaction [42][43][44]. It was suggested that part of the chemopreventive effect of MSC is due to β-elimination of methylselenol [CH 3 SeH] from MSC [45]. Transamination of MSC yields βmethylselenopyruvate [MSP; CH 3 SeCH 2 C(O)(CO 2 − )] [42].…”
Section: L-glutamine Transaminases Catalyzementioning
confidence: 99%
“…In a recent publication, Selvam et al showed that introduction of high levels of GTK into hepatocellular carcinoma cell lines greatly enhanced the cytotoxicity of MSC, possibly as a result of increased oxidative stress [45]. The effect was even more pronounced in the presence of α-keto acid substrates of GTK/GTL, namely, phenylpyruvate and αketo-γ-methiolbutyrate (KMB; synonyms: 4-methylthio-2-oxobutanoate, 4-methylthio-2oxobutyrate) [45].…”
Section: L-glutamine Transaminases Catalyzementioning
confidence: 99%